2017
DOI: 10.3390/nano7060120
|View full text |Cite
|
Sign up to set email alerts
|

Trigger-Responsive Gene Transporters for Anticancer Therapy

Abstract: In the current era of gene delivery, trigger-responsive nanoparticles for the delivery of exogenous nucleic acids, such as plasmid DNA (pDNA), mRNA, siRNAs, and miRNAs, to cancer cells have attracted considerable interest. The cationic gene transporters commonly used are typically in the form of polyplexes, lipoplexes or mixtures of both, and their gene transfer efficiency in cancer cells depends on several factors, such as cell binding, intracellular trafficking, buffering capacity for endosomal escape, DNA u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 180 publications
0
14
0
Order By: Relevance
“…3 Since naked nucleic acids have poor internalization and the tendency for lysosomal degradation, non-viral carriers have been developed to compact genes and deliver them into target cells. [4][5][6] Nanoparticles, because of their unique properties, including adjustable size, morphology and surface characteristics, have been widely researched as non-viral gene carriers. [7][8][9][10] To realize satisfying gene transfection, non-viral gene delivery system must overcome various extracellular and intracellular barriers.…”
Section: Introductionmentioning
confidence: 99%
“…3 Since naked nucleic acids have poor internalization and the tendency for lysosomal degradation, non-viral carriers have been developed to compact genes and deliver them into target cells. [4][5][6] Nanoparticles, because of their unique properties, including adjustable size, morphology and surface characteristics, have been widely researched as non-viral gene carriers. [7][8][9][10] To realize satisfying gene transfection, non-viral gene delivery system must overcome various extracellular and intracellular barriers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, replacement of the hydrophobic residues with hydrophilic rendered the resultant peptide (RGSG) incapable of transfection (Udhayakumar et al 2017 ). To date, RALA has successfully delivered plasmids encoding reporter genes (McCarthy et al 2014 ), mRNA (Udhayakumar et al 2017 ), siRNA (Bennett et al 2015 ), DNA vaccines (Rajendrakumar et al 2017 ), mRNA vaccines (Udhayakumar et al 2017 ) small molecules such as bisphosphonates (Massey et al 2016 ) and calcium-based bone substitutes (Huerta et al 2008 ) demonstrating broad utility.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic origins of cancer render suitability for gene therapeutics such as small interfering RNAs, micro RNAs, and CRISPR gene editing tools (Rajendrakumar et al 2017 ). Indeed, previous research has reported abrogation of the growth of ZR-75-1 breast cancer xenografts when treated with RALA/pFKBPL (Bennett et al 2015 ), and the potency of RALA-delivered inducible nitric oxide synthase (iNOS) in a model of breast cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy has been regarded as a promising therapeutic approach for cancer, neurodegenerative diseases, and viral infections . However, naked nucleic acids require protection by carriers for delivery into target cells and obtain efficient gene expression or target protein silencing . Cellular uptake is the first step for internalization, and endocytosis is 1 of the major pathways for cellular uptake of nanosized nucleic acid delivery systems .…”
Section: Introductionmentioning
confidence: 99%